Scandinavians in the State House : How Nordic Immigrants Shaped Minnesota Politics - Bergman, Klas, 1942- (Book collections on Project MUSE., 2017)
"This is the story of immigration and politics, or more precisely the story of Scandinavian immigrants in Minnesota and their role, impact, and legacy in Minnesota politics"--Page 1.